Adsorption studies of mussel-inspired peptides. Issue 1 (1st March 2013) - Rischka, Klaus; Müller, Frank A.; Diaconu, Gabriela; Amkreutz, Marc; Richter, Katharina; Hartwig, Andreas
Abstract : A decapeptide sequence derived from the blue mussel protein (mefp 1) was modified in order to study the effect of the sequence length and the content of the amino acid 3, 4-dihydroxyphenylalanine (DOPA) on the peptides adsorption properties. These modifications involved varying DOPA content ( n = 0; 1; 2; 4) and varying peptide sequence repetition number ( x = 1; 2). The adsorption properties of these peptides were determined by quartz crystal microbalance (QCM) measurements on TiO2 and SiO2 substrates and diametrically opposed trends were observed. A key aspect of the work was to study the effect of oxidation of DOPA-containing peptides on the adsorption. This effect was examined by X-ray photoelectron spectroscopy on TiO2 substrates and augmented the QCM measurements. The results presented here provide information about the interplay between size and the DOPA content of the peptide. The results for titanium showed an increase in adsorption for a higher DOPA content, while the effect was more distinct for the shorter peptides. On the basis of these observations, possible explanations are given for the sequence length differences and the variation of the DOPA groups within mussel proteins.